MEDICINAL PLANTS AS A GENERATIVE THEME FOR THE STUDY OF ORGANIC FUNCTIONS AND SCIENTIFIC LITERACY IN CHEMISTRY - Cruz , Jaine Costa; de Freitas, Rita de Cássia Ramos Queiroz; Queiroz, Maria Sandra Ramos; Neves, Luís Henrique Pereira; de Souza, Cassius; de Castro, Symone Costa; Junior, Ivanilson Vieira Souza; Santana, Jane Geralda Ferreira (Seven Editora, 2024)
Chemistry teaching requires the use of approaches that provide students with conditions so that they can critically interpret the reality in which they live. This implies the need to link the content worked with the social context in which the student is inserted. However, the practice of contextualizing is rarely addressed in the classroom, especially when it comes to teaching Organic Chemistry. Therefore, this research aimed to propose a didactic intervention based on the theme of medicinal plants as a proposal to integrate the student's daily life with the construction of knowledge about Organic Functions, in order to make the teaching and learning process more meaningful in accordance with the proposal for Scientific Literacy. The research was carried out with students from a 3rd year class of Integrated Technical High School in Computer Science for the Internet at the Federal Institute of Education Science and Technology Baiano - Campus Guanambi, in the period between November 2022 and May 2023 and involved six stages, with diverse activities. The use of the theme met the objectives of the study proposal, as, depending on the receptivity of the participants, it constitutes a teaching resource that brought the study of Organic Functions closer to everyday life, favoring more meaningful learning. The proposed use of the generating theme also demonstrated that it aroused the students' curiosity and interest, given their active participation in the construction of knowledge, which may have contributed to the teaching and scientific literacy processes. DOI:https://doi.org/10.56238/sevened2024.027-002